r 2008
DOI: 10.20955/r.90.9-30
|View full text |Cite
|
Sign up to set email alerts
|

The Microfinance Revolution: An Overview

Abstract: The Nobel Prize committee awarded the 2006 Nobel Peace Prize to Muhammad Yunus and the Grameen Bank "for their efforts to create economic and social development from below." The microfinance revolution has come a long way since Yunus first provided financing to the poor in Bangladesh. The committee has recognized microfinance as "an important liberating force" and an "ever more important instrument in the struggle against poverty." Although several authors have provided comprehensive surveys of microfinance, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
88
2
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(97 citation statements)
references
References 25 publications
0
88
2
7
Order By: Relevance
“…"Real estate value" is the dollar value, estimated by the credit officer at the loan grant date, of land and house owned by the household. Although real estates do not formally guarantee the loan, contrary to a common wisdom that microcredit is typically addressed to people who do not own any valuable assets (Pankaj, 1996;Sengupta & Aubuchon, 2008), we found an average asset value of 8,000 USD (e.g., more than ten times the national GDP per capita).…”
Section: Data Collectioncontrasting
confidence: 89%
“…"Real estate value" is the dollar value, estimated by the credit officer at the loan grant date, of land and house owned by the household. Although real estates do not formally guarantee the loan, contrary to a common wisdom that microcredit is typically addressed to people who do not own any valuable assets (Pankaj, 1996;Sengupta & Aubuchon, 2008), we found an average asset value of 8,000 USD (e.g., more than ten times the national GDP per capita).…”
Section: Data Collectioncontrasting
confidence: 89%
“…They concluded that microfinance could only become an effective device to fight against poverty if it could reach the poorest user of microfinance. Opponents of microfinance argued that Microfinance institutes had to distinguish between "marginally poor" and "very poor" (Sengupta and Aubuchon, 2008). Because of gender disparities in distribution of earnings, access to credit, lack of control over property and earnings, gender preferences in labor markets, women encountered many more dimensions of poverty in their real life (Cagatay, 1998).…”
Section: Asian Economic and Financial Reviewmentioning
confidence: 99%
“…This article exercise other financing scenario in which all stakeholders are entitled for profit sharing instead of purely fully paid parties. In terms of financing to smallholder farmers, Gupta & Aubuchon (2008) claimed that microfinance proved to improve the lives of the poor farmers. In line with Gupta & Aubuchon (2008), Latief et al (2011) stated that microcredit in Pakistan had positive impact in alleviating poverty in which farmers were able to borrow money at lower bank rates and start a small business.…”
Section: Research Frameworkmentioning
confidence: 99%
“…In terms of financing to smallholder farmers, Gupta & Aubuchon (2008) claimed that microfinance proved to improve the lives of the poor farmers. In line with Gupta & Aubuchon (2008), Latief et al (2011) stated that microcredit in Pakistan had positive impact in alleviating poverty in which farmers were able to borrow money at lower bank rates and start a small business. In contrast, Adams & Bartholomew (2010) stated that in Ghana, the impact of microfinance for farmers were socially and financially marginal.…”
Section: Research Frameworkmentioning
confidence: 99%